Analysis Support Families With Quality Of Life After Stroke Patients - Heri Saputro; Mariana Ina Camo; Budi Suraksono; Dhita Kurnia Sari; Sri Kardjati (STRADA : Jurnal Ilmiah Kesehatan, 2019)
The study design was cross-sectional descriptive correlative approach. Data collection tool is a questionnaire guide. Sample of 35 respondents using accidental sampling technique. The independent variable in this study is the family support and the dependent variable quality of life of patients with post-stroke. The results showed 16 respondents, or 45.8% of respondents received sufficient family support. Respondents who have a sufficient quality of life amounted to 15 respondents or 42.7%. By Spearman Rho obtained significance value (p value = 0.00) <(α = 0.05), which proved to be no family support relationships with the quality of life of the elderly after a stroke. Post-stroke patients have problems of physical health, psychological, level of dependence, social relationships, environment and personal beliefs. Therefore, they need emotional support, awards, instrumental and information, especially of the family as the people closest to them thus improving patient quality of life after stroke